1991
DOI: 10.1037/0278-7393.17.5.924
|View full text |Cite
|
Sign up to set email alerts
|

The level-of-focal-attention hypothesis in oral reading: Influence of strategies on the context specificity of lexical repetition effects.

Abstract: Two experiments examined the influence of level of focal attention--text or lexical--on benefits from lexical repetition in speeded oral reading of coherent texts and random word lists. Experiment 1 showed that with coherent targets, direction of attention to the text level resulted in benefit only from a previous reading of the same coherent paragraph. However, when attention was directed to the lexical level, equal benefit resulted from a previous reading of either the same coherent paragraph or a scrambled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
36
1

Year Published

1992
1992
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(40 citation statements)
references
References 17 publications
3
36
1
Order By: Relevance
“…It is difficult, though, to compare the relative sizes of these effects, given that we have no method of de- termining the relative impacts of short-term repetition of unfamiliar sentences versus long-term retention of classic rhymes on the attention given to individual words. However, others have speculated that reading aloud tends to draw attention to the lexical level of processing (see, e.g., Carlson et al, 1991), perhaps thereby encouraging unitization of individual words that in turn might enhance the MLE.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is difficult, though, to compare the relative sizes of these effects, given that we have no method of de- termining the relative impacts of short-term repetition of unfamiliar sentences versus long-term retention of classic rhymes on the attention given to individual words. However, others have speculated that reading aloud tends to draw attention to the lexical level of processing (see, e.g., Carlson et al, 1991), perhaps thereby encouraging unitization of individual words that in turn might enhance the MLE.…”
Section: Discussionmentioning
confidence: 99%
“…One curious finding was that five repetitions produced no greater effect than did two repetitions. Perhaps reading the text aloud puts so much focus on each individualword that the effects reach some asymptote with only two repetitions (see, e.g., Carlson, Alejano, & Carr, 1991, regarding effects of reading words aloud).…”
Section: Discussionmentioning
confidence: 99%
“…Carr, Brown, and Charalambous (1989) found equivalent performance on the second reading of texts whether the first reading was scrambled or coherent, which led them to suggest that word-level factors were responsible for the speed-up. However, subsequent research by Carlson, Alejano, and Carr (1991) showed that this result happened because the task set conveyed in the instructions induced subjects to attend to words and ignore text-level structures. When Carlson et al (1991) induced subjects to attend to the meanings of paragraphs, they found that the second reading was faster if the first were coherent than if it were scrambled, indicative of text-level automaticity.…”
Section: Text-level Automaticitymentioning
confidence: 99%
“…However, subsequent research by Carlson, Alejano, and Carr (1991) showed that this result happened because the task set conveyed in the instructions induced subjects to attend to words and ignore text-level structures. When Carlson et al (1991) induced subjects to attend to the meanings of paragraphs, they found that the second reading was faster if the first were coherent than if it were scrambled, indicative of text-level automaticity. Levy and Burns (1990) compared coherent texts with texts that were scrambled by reordering paragraphs, sentences, and words.…”
Section: Text-level Automaticitymentioning
confidence: 99%
“…That is, lexical representations of individual word units were primed during the first reading, so that later rereading of these units was faster and more accurate. Carr and his associates were the main advocates of this position (Brown & Carr, 1993;Carlson, Alejano, & Carr, 1991;Carr & Brown, 1990;Carr, Brown, & Charalambous, 1989). Carr et al asked participants to read and reread aloud paragraphs that were in normal form or were scrambled word versions of the paragraphs.…”
mentioning
confidence: 99%